CCAAT/Enhancer-binding Protein-Homologous Protein Sensitizes to SU5416 by Modulating p21 and PI3K/Akt Signal Pathway in FRO Anaplastic Thyroid Carcinoma Cells - Kim, S. H.; Kang, J. G.; Kim, C. S.; Ihm, S.-H.; Choi, M. G.; Yoo, H. J.; Lee, S. J. (Hormone and Metabolic Research, 2013)
SU5416, vascular endothelial cell growth factor receptor inhibitor, suppresses hypoxia-induced angiogenesis, growth, proliferation, and metastasis in cancer cells. CCAAT/enhancer-binding protein-homologous protein (CHOP) has pivotal roles in regulation of growth and survival. In the present study, we evaluated the effects of SU5416 on cell survival, p21, and PI3K/Akt signal pathway in FRO anaplastic thyroid carcinoma (ATC) cells. Moreover, we investigated the roles of CHOP in cell survival under condition of SU5416 treatment in FRO ATC cells. After SU5416 treatment, cell viability, PARP-1, and caspase-3 protein levels were not changed. p53 and p27 protein levels decreased while p21 protein levels increased. Phospho-Akt protein levels were not altered. In SU5416-treated situation, cell viability was not different before and after administration of either p21 siRNA or LY294002 whereas it was lessened after co-administration of p21 siRNA and LY294002. Compared to SU5416 treatment alone, cell viability was reduced with CHOP plasmid but it was unchanged with CHOP siRNA. PARP-1 and caspase-3 protein levels with CHOP plasmid were elevated whereas the protein levels with CHOP siRNA were similar. While CHOP plasmid transfection diminished p21 and phospho-Akt protein levels, CHOP siRNA transfection did not alter the protein levels. In conclusion, these results suggest that CHOP may sensitize FRO ATC cells to SU5416 thereby inhibiting cell survival by modulating p21 and PI3K/Akt signal pathway. Furthermore, these findings imply that CHOP may be a possible candidate as the chemosensitizing factor for induction of cytotoxicity in ATC cells exposed to SU5416.
Keywords: anaplastic thyroid carcinoma; SU5416; CCAAT/enhancer-binding protein-homologous protein; p21; Akt